Artificial Intelligence as an Innovative Technology for Digital Promotion of Solo’s Culinary Heritage towards Sustainable - Slamet Kurniawan Fahrurozi; Annisa Noor Rachmawati; Dimas Pamilih Epin Andrian (SAINTIS Publishing, 2025)
This study investigates the role of artificial intelligence (AI) as an innovative technology for promoting Solo’s culinary heritage and its contribution to sustainable tourism. Using a mixed-method approach, the research employed the ARF (Attention, Branding, Communication, Motivation, Emotional Response, Memory/Recall, Purchase Intent) and AIDA (Attention, Interest, Desire, Action) models to evaluate consumer responses. Data were collected from 100 respondents through questionnaires and from 20 participants via qualitative discussions. The quantitative findings indicate that AI-driven promotional materials are effective in generating awareness and positive perceptions, particularly in attention (M = 4.05) and communication (M = 3.92), but less effective in driving direct consumer action (M = 3.42). Qualitative insights highlight the importance of cultural authenticity and the need to balance technological innovation with human-centered narratives. Moreover, the study demonstrates AI’s contribution to sustainable tourism across four dimensions: economic (supporting small businesses), cultural (preserving heritage), social (enhancing inclusivity and engagement), and environmental (reducing waste through predictive analytics). In conclusion, AI emerges as a powerful tool not only for digital promotion but also as a catalyst for sustainable tourism development. The integration of AI into culinary promotion offers a replicable model for other cities seeking to balance economic growth, cultural preservation, and sustainability in line with the United Nations Sustainable Development Goals (SDGs).